2018
DOI: 10.1017/jns.2018.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gene polymorphisms of metabolic enzymes on the association between red and processed meat consumption and the development of colon cancer; a literature review

Abstract: The role of environmental factors and genetic susceptibility in the development of colon cancer (CC) has been already proven, but the role of gene polymorphisms in modifying the risk of environmental factors such as nutritional factors is still unknown. This study aimed to investigate the effect of polymorphisms of involved genes in the association between red meat consumption and the development of CC. The present review was carried out using keywords such as polymorphism and/or protein and/or red meat and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…Phytosterols in the Aloe vera can alter the steroidogenic response and express estrogen receptor protein, reduce androgens, increase estrogens, and ultimately improve the conditions of the PCOS. Aloe vera phytosterols such as sitosterol reduce serum cholesterol levels and normalized (3β-Hydroxysteroid dehydrogenase) 3βHSD activity in PCOS rats [15,17,18].…”
Section: Aloe Veramentioning
confidence: 99%
See 1 more Smart Citation
“…Phytosterols in the Aloe vera can alter the steroidogenic response and express estrogen receptor protein, reduce androgens, increase estrogens, and ultimately improve the conditions of the PCOS. Aloe vera phytosterols such as sitosterol reduce serum cholesterol levels and normalized (3β-Hydroxysteroid dehydrogenase) 3βHSD activity in PCOS rats [15,17,18].…”
Section: Aloe Veramentioning
confidence: 99%
“…Aloe vera is a medicinal plant with hypoglycemic effects [13,15,16]. Aloe vera is rich in fiber which accelerates gastrointestinal transit, absorption, and modulation of hemostasis [15][16][17] Aloe vera contains many compounds with different potential biological activities. Phytosterols in the Aloe vera can alter the steroidogenic response and express estrogen receptor protein, reduce androgens, increase estrogens, and ultimately improve the conditions of the PCOS.…”
Section: Aloe Veramentioning
confidence: 99%
“…Obesity has been dramatically increased over the last two decades in both low and high-income countries [1]. Obesity is a risk factor for the other diseases such as cardiovascular disease, type 2 diabetes, hypertension, and psychological disorders [2][3][4]. The prevalence of obesity was also recently increased in Iran and more than 50% of the Iranian population is obese or overweight.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity was also recently increased in Iran and more than 50% of the Iranian population is obese or overweight. Some genes such as the fat mass and obesityassociated (FTO) gene are strongly associated with obesity and overweight [4].…”
Section: Introductionmentioning
confidence: 99%
“…Another area of genetics that is associated with cancer is gene polymorphism and its susceptibility to colon cancer in the context of environmental factors such as nutrition [68]. In particular, the association between red meat consumption and the development of colon cancer, and the presence of single nucleotide polymorphisms (SNPs) in the coding genes of the proteins involved in the metabolism of nutrients have been investigated [68]. It has been demonstrated that gene polymorphisms might have a role to play in colorectal cancer risk in individuals consuming large quantities of red meat.…”
Section: Cancer and Geneticsmentioning
confidence: 99%